Spatial Perception Of The Street As A Feature Of The Sustainable Development Of The Cities Of The Eastern High Plateaus: street 8 May 1945 In The City Of Setif - Salhi, Atef; Boulehouache, Alaoua (Journal of Architecture and environment of child, 2023)
Within the framework of the sustainable development goals, the developmental and tourism dimension is of significant value. It affects the economy and it is able to highlight the symbolism of the place. The attractive places that characterize a city show well this dimension. This research takes place at the eastern high plateaus of Algeria, in the state of Setif. The city of Setif possesses many historical landmarks which still attract different segments of society. May 8, 1945 Street also known as Ain El Fouara Street is characterized by its spaciousness, urban facades, and corridors of historical dimension. It also has commercial, service and entertainment activities alike. This study relies on these functional and formal criteria to highlight the strength of the local and regional attraction force. It enables the identification of formal and functional criteria for the future planning of avenues in the cities of the eastern Algerian high plateaus. This guarantees the city an important role in sustainable development.